2015
DOI: 10.1186/s12957-015-0660-0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal intussusception in a young women: unusual cause and specific management

Abstract: BackgroundIntussusception in adults is a rare cause of abdominal pain that is often associated with organic pathology. We describe a case of ileocolic intussusception revealing a cecal adenocarcinoma in a young woman successfully managed by laparoscopic-assisted surgery adhering to oncological principles.Case presentationA 30-year-old woman with a family history of colon adenocarcinoma in a young brother presented to our emergency department with a 2-month history of intermittent colicky abdominal pain accompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…12 In adults, the clinical presentation of intussusception can be nonspecific, rarely presenting with the classic triad of abdominal pain, palpable mass, and bloody stool. [13][14][15] Instead, it presents with symptoms of small or large bowel obstruction. The most common presenting symptom is abdominal pain, 14,16 with associated symptoms consistent with partial obstruction: nausea, vomiting, obstipation, gastrointestinal bleeding, change in bowel habits, constipation, or bloating.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In adults, the clinical presentation of intussusception can be nonspecific, rarely presenting with the classic triad of abdominal pain, palpable mass, and bloody stool. [13][14][15] Instead, it presents with symptoms of small or large bowel obstruction. The most common presenting symptom is abdominal pain, 14,16 with associated symptoms consistent with partial obstruction: nausea, vomiting, obstipation, gastrointestinal bleeding, change in bowel habits, constipation, or bloating.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…1-4). 13,14,19 Additionally, mesenteric vessels within the bowel lumen are characteristic on CT, showing compromised vascular perfusion in terms of venous stasis, edema, and air in the bowel wall due to necrosis or gangrene. 14 Despite the benefits of CT, Martín-Lorenzo et al found that while CT is extraordinarily sensitive for detecting intussusception, it is limited by less accessibility, a static and single plane exploration, radiation, and finally oral and IV contrast which could further delay the study and thus the proper diagnosis.…”
Section: Patient Evaluationmentioning
confidence: 99%
“…Successful endoscopic resection has been reported for benign lesions causing intussusception,13 but should be dealt with caution due to increased risk of complications. Minimal invasive surgery for resection of the involved segment is also possible in expert hands, decreasing the pain and hospital stay 14…”
Section: Discussionmentioning
confidence: 99%
“…En los adultos, la presentación clínica de la invaginación intestinal es más inespecífica y rara vez se presenta con la tríada clásica de dolor abdominal, masa palpable y heces sanguinolentas (18). Por el contrario, suele presentarse con síntomas de obstrucción intestinal.…”
Section: Presentación Clínicaunclassified